A course in business statistics - Mendenhall, William; Beaver, Robert J.; Beaver, Barbara M. (Belmont, CA : Duxbury Press, 1996)
This book is about: What is statistics; Describing sets of data; Probability and discrete probability distributions; ...
Keywords: Commercial statistics; Commercial statistics